Global patterns of terrestrial assemblage turnover within and among land uses. Issue 12 (26th February 2016) - Newbold, Tim; Hudson, Lawrence N.; Hill, Samantha L. L.; Contu, Sara; Gray, Claudia L.; Scharlemann, Jörn P. W.; Börger, Luca; Phillips, Helen R. P.; Sheil, Douglas; Lysenko, Igor; Purvis, Andy
Abstract : Land use has large effects on the diversity of ecological assemblages. Differences among land uses in the diversity of local assemblages (alpha diversity) have been quantified at a global scale. Effects on the turnover of species composition between locations (beta diversity) are less clear, with previous studies focusing on particular regions or groups of species. Using a global database on the composition of ecological assemblages in different land uses, we test for differences in the between‐site turnover of species composition, within and among land‐use types. Overall, we show a strong impact of land use on assemblage composition. While we find that compositional turnover within land uses does not differ strongly among land uses, human land uses and secondary vegetation in an early stage of recovery are poor at retaining the species that characterise primary vegetation. The dissimilarity of assemblages in human‐impacted habitats compared with primary vegetation was more pronounced in the tropical than temperate realm. An exploratory analysis suggests that this geographic difference might be caused primarily by differences in climate seasonality and in the numbers of species sampled. Taken together the results suggest that, while small‐scale beta diversity within land uses is not strongly impacted by land‐use type, compositional turnover between land uses is substantial. Therefore, land‐use change will lead to profound changes in the structure of ecological assemblages.